METHODOLOGY OF TEACHING A COURSE OF PULMONOLOGY TO STUDENTS WITH A FOREIGN FORM OF EDUCATION - Савеліхіна, І. О.; Островська, К. М.; Варунків, О. І.; Кулинич-Міськів, М. О.; Корж, Г. З.; Островський, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the education system of Ukraine, the concept of training doctors is being developed in accordance with the requirements of the World Federation of Medical Education and the main provisions of the Bologna Process. One of the participants in the implementation of reforms and innovations in medicine of Ukraine is the Ivano-Frankivsk National Medical University. The modern level of education changes the types and forms of teaching, the conditions of which are motivativnost, dynamism, flexibility, activation of thinking, decision-making in specific situations. Along with the intensification of training due to the professional and pedagogical skills of teachers on the use of advanced technologies, new methods of exercises that increase motivation, professionalism, and activity, bring more efficiency every day. In our country there are all conditions that would shape the interest of future physicians in obtaining a profession, aspiration for self-improvement and highlight the issue of improving the quality of vocational training. In order to increase the rating and the level of higher education in Ukraine, the positive role is played by the positive dynamics of the number of students in higher education in English. The features of teaching a course of pulmonology to students with an English language form of education are outlined. The positive role of the new computer technologies of the educational process in the organization of independent work of the student during the academic time is noted. The acquired knowledge in the field of pulmonology will contribute to the formation of clinical thinking and improve the quality of training and competitiveness of the doctors.